SUATU TINJAUAN PEMANFAATAN KAYU HUTAN TANAMAN UNTUK GLULAM - Yusuf Sudo Hadi; Andi Sri Rahayu Diza Lestari (Jurnal Penelitian Hasil Hutan, 2022)
Plantation forests is generally harvested at the age of less than 10 years, thus the log is in small diameter, inferior physicalmechanical properties, and susceptible to bio-deterioration. The application of glued-laminated timber (glulam) could overcome theseissues and increase its utilization. This paper reviews the utilization of wood from plantation forest for glulam. Currently, woodfrom plantations forest studied in glulam research were jabon (Anthocephalus cadamba), rubber-wood (Hevea brasiliensis),mahogany (Swietenia sp.), mangium (Acacia mangium), manii (Maesopsis eminii), mindi (Melia azedarach), pine(Pinus merkusii), sengon (Falcataria moluccana), and sungkai (Peronema canescens). Kempas wood (Koompassiamalaccensis) and merbau (Intsia sp.) from natural forests were used as a layer combination of the glulam. The adhesives usedfor manufacturing glulam were tannin-based adhesives from mangium, mahogany, and merbau, as well as synthetic adhesives,namely isocyanate and phenol resorcinol formaldehyde (PRF). The results shows that glulam bonded with tannin-based adhesivehas physical-mechanical properties comparable with those of solid wood and glulam adhered with PRF adhesive. The physicalmechanical properties of glulam glued with isocyanate were similar with its solid wood. However, the shear strength of glulam waslower than solid wood. There was no delamination occurred in both cold and boiling water delamination tests. Thus, it fulfilledJAS 1152- 2007. The polystyrene impregnation applied in sengon and mindi glulams manufacturing resulted in a few effect ofcolor change, comparable shear strength to its solid wood, and increases its resistance to subterranean termites (Coptotermescurvignathus Holmgren) attack.